Recurrent Giant Parasagittal Meningioma WHO Grade I: A Case Report Highlighting the Challenges of Management and the Role of Molecular Markers - Sumargo, Sheila; Selfy Oswari; Guata Naibaho; Roland Sidabutar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Meningiomas are common intracranial tumors, but their recurrence, especially in giant parasagittal locations, presents significant management challenges. This case report underscores these challenges and emphasizes the potential role of molecular markers in improving prognostication and treatment strategies. Case presentation: A 31-year-old female presented with recurrent giant parasagittal meningioma WHO Grade I. She underwent multiple surgeries and embolizations due to persistent tumor regrowth despite histologically benign features. The tumor's location, size, and involvement of critical structures posed surgical difficulties, highlighting the limitations of current management approaches. Conclusion: This case emphasizes the need for a more nuanced understanding of meningioma recurrence beyond histological grading. Molecular markers may offer valuable insights into tumor behavior and guide personalized treatment decisions, potentially improving outcomes for patients with recurrent meningiomas.